2018
DOI: 10.1155/2018/6078457
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Orofacial Pain Therapy in Indonesia: A Cross-Sectional Study

Abstract: Objective(s) As the most complained oral problems in Indonesia, the therapy of orofacial pain has to be constantly evaluated. The objective of the current study was to evaluate the effectiveness of orofacial pain therapy in Indonesia. Method(s) This study recruited 5412 (3816 female; 1596 male) participants from 27 districts in West Java province. Half of the participants (2714) were recruited from those who were treated at community health centers whilst the rest were those who were treated at private dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In Indonesia, a study that was conducted on 5,412 participants aged 18 years old and older revealed that 2,892 of the participants experienced dental pain in the last 6 months. 5 Aside from its high prevalence, dental pain is also known for its impacts on the sufferer's (oral health) quality of life. 2,6,7 In a study conducted by Samuel et al about the impact of dental pain on the patient's oral health quality of life (OHQoL), it was reported that higher self-reported pain score and longer pain duration negatively impact the OHQoL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, a study that was conducted on 5,412 participants aged 18 years old and older revealed that 2,892 of the participants experienced dental pain in the last 6 months. 5 Aside from its high prevalence, dental pain is also known for its impacts on the sufferer's (oral health) quality of life. 2,6,7 In a study conducted by Samuel et al about the impact of dental pain on the patient's oral health quality of life (OHQoL), it was reported that higher self-reported pain score and longer pain duration negatively impact the OHQoL.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, a study that was conducted on 5,412 participants aged 18 years old and older revealed that 2,892 of the participants experienced dental pain in the last 6 months. 5 …”
Section: Introductionmentioning
confidence: 99%
“…(Subashri and Maheshwari, 2016) Based on etiology, Orofacial pain has been classi ied into the seven following categories: (Rezaei et al, 2017;Maheswari et al, 2018) The neurologic pain category which includes cranial neuralgia, nerve trunk pain and differentiation pain, has further been classi ied into (Rezaei et al, 2017) The prevalence of Orofacial Pain (OFP) has been assuming variations in different populations, based on the etiology involved. According to Maulina (2018), the prevalence of Orofacial pain in the Indonesian population was high, and a signi icant correlation between the monthly income and pain in TMJ has been reported (Saman et al, 2019;Misra et al, 2015). In the Portuguese population, only 5 -15% reported with Orofacial Pain as their primary complaint.…”
Section: Introductionmentioning
confidence: 99%